2000
DOI: 10.1063/1.1312848
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum impurities in silicon: Investigation of x-ray Raman scattering in total reflection x-ray fluorescence spectroscopy

Abstract: Total Reflection X-ray Fluorescence (TXRF) using Synchrotron Radiation from the Stanford Synchrotron Radiation Laboratory (SSRL) has been used to study Al impurities on Si wafer surfaces. For primary excitation energies below the Si K absorption edge an inelastic resonance scattering due to resonant xray Raman scattering is observed. This scattering dominates the background behavior of the Al K fluorescence line, and consequently limits the achievable sensitivity for detection of Al surface contaminants. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…2 However, the latter can be overcome by tuning the primary x-ray energy to an excitation energy below the Si K absorption threshold which also increases the photo absorption cross-section for Al [5,6]. This results in a minimum detection limit of 2.4 x 10 9 atoms/cm 2 as will be shown below.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 However, the latter can be overcome by tuning the primary x-ray energy to an excitation energy below the Si K absorption threshold which also increases the photo absorption cross-section for Al [5,6]. This results in a minimum detection limit of 2.4 x 10 9 atoms/cm 2 as will be shown below.…”
Section: Introductionmentioning
confidence: 99%
“…This background is due to resonant inelastic x-ray Raman scattering which is an inelastic x-ray scattering process [10,11,12]. It has been shown that the asymmetric shape of the x-ray Raman scattering dominates the background of the Al fluorescence line.In order to accurately determine the minimum detection limit, the spectra have to be deconvoluted taking the specific shape of the resonant Raman scattering profile into account [6].In this paper we demonstrate that this data analysis can also be extended for the deconvolution of TXRF spectra from conventional systems which so far only subtract the background as measured from a clean Si wafer. A deconvolution of the Al spectra would make this step unnecessary and could increase the accuracy in determining the Al concentration on Si wafer surfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, as reported earlier, 6,14,15 the DL for Al is affected by the presence of the x-ray resonant Raman scattering ͑RRS͒ process in Si. Indeed, for photon beam energies tuned below the Si K-edge in order to avoid the strong K␣ fluorescence line, the x-ray RRS profile overlaps with the weak fluorescence line from Al impurities.…”
mentioning
confidence: 53%
“…The cross-section for X-ray Raman scattering is generally low compared to the elastic Rayleigh or inelastic Compton scattering, but it can become significant due to resonant enhancement if the incident photon energy is close to a major absorption edge of the sample matrix. Figure 3 shows a typical fluorescence spectrum (dots) from a wafer intentionally contaminated with 3 ϫ 10 11 atoms/cm 2 aluminum obtained for an excitation energy of 1730 eV and an angle of incidence of 0.1°(critical angle = 0.9°) for 10,000 s. The figure also contains the deconvolved contribution from the elastically scattered signal at 1730 eV, the aluminum K␣ line, and the calculated continuous Raman background (18). This figure demonstrates that it is the inelastic Raman scattering that ultimately determines the minimum detection limit for aluminum, which has been derived for a bending magnet beamline to be 2.4 ϫ 10 9 atoms/cm 2 for a 10,000-s count time, corresponding to 7.6 ϫ 10 9 atoms/cm 2 for a standard 1000-s count time.…”
Section: Sensitivitymentioning
confidence: 99%